Rethinking implicit memory - Bowers, Jeffrey S.; Marsolek, Chad J. (Oxford University Press, 2003)
Implicit memories are items of information stored in the absence of conscious awareness - though they cannot be deliberately recalled, they can be tested by indirect means. This title examines the data the topic has produced.